No effect of a musical intervention on stress response to venepuncture in a neonatal population. (18th October 2019) - Howard, Caoimhe; Powell, Anna S.; Pavlidis, Elena; Pavel, Andreea; Finn, Daragh; Allen, Andrew; Olavarria‐Ramirez, Loreto; Clarke, Gerard; Livingstone, Vicki; Boylan, Geraldine B.; Dempsey, Eugene M.
Abstract: Aim: To investigate the effect of a musical intervention on neonatal stress response to venepuncture as measured by salivary cortisol levels and pain profile scores. Methods: In a randomised control crossover trial, participants were randomised to both a control arm (sucrose) and intervention arm (sucrose and music) for routine venepuncture procedures. Salivary swabs were collected at baseline, 20 minutes post‐venepuncture and 4 hours post‐venepuncture. Pain levels were assessed using the Premature Infant Pain Profile (PIPP). A total of 16 preterm neonates participated in both arms to complete the study. Results: Cortisol values were elevated at all timepoints in the intervention arm (baseline, 20 minutes, and 4 hours post‐procedure) but not significantly so ( P = .056, P = .3, and P = .575, respectively). Median change in cortisol values from baseline was +128.48 pg/mL (−47.66 to 517.02) at 20 minutes and +393.52 pg/mL (47.88‐1221.34) at 4 hours post‐procedure in the control arm compared to −69.564 pg/mL (−860.96 to 397.289) and +100.48 pg/mL (−560.46 to 842.99) at 20 minutes and 4 hours post‐procedure in the intervention arm. There was no statistically significant difference observed between groups ( P = .311 at 20 minutes, and P = .203 at 4 hours post‐procedure). PIPP scores were not significantly different between study arms. Conclusion: Our findings did not support the additional benefit of music intervention on neonatal stress response to venepuncture in preterm infants.